YOUTH OF POPULAR CULTURE IN THE CONDITIONS OF GLOBALIZATION IMPACT ON WORLDVIEW (World Bulletin of Management and Law, 2023)
In this article, the impact of popular culture on the worldview of young people in the context of globalization. Its negative consequences have been scientifically analyzed. Today, as a result of the intensification of the rapid flow of information, the breadth of its scope, universal processes related to universal technologies have a serious impact on the worldview of young people. Especially young people are turning into the age of various entertainment shows distributed through social networks. Analyzing such shows, which can negatively affect the morals of young people, and explaining their negative consequences on a scientific basis remains one of the urgent issues of today. Globalization plays an important role in the exchange of information in the world community. However, some information is biased and aimed at misleading young people from the right path, so they should be protected from such negative situations. They should be educated to follow the rules that are in the interest of the society.
Keywords: Globalization; mass culture; universal technologies; brainstorming